Muhammadiyah di Kulon Progo (1926–2024): Kajian Historis tentang Dinamika Organisasi dan Kontribusi Sosial-Keagamaan - Adam Kaneka Putra; Siska Nurazizah Lestari; Nuryuana Dwi Wulandari (Medan Resource Center, 2026)
This study examines the historical development and socio-religious role of Muhammadiyah in Kulon Progo from 1926 to 2024 within the dynamics of local Islamic organizations. Using historical research methods—heuristic data collection, source criticism, interpretation, and historiography—it analyzes archival records, organizational documents, and oral testimonies to trace institutional transformation. The findings identify three major phases: consolidation during the late colonial and early independence periods; expansion of educational and health institutions during the New Order; and diversification of social engagement in the Reformasi era. Muhammadiyah functioned not only as a religious movement but also as a local agent of modernization through schools, healthcare services, and community-based programs. Its autonomous bodies, including ‘Aisyiyah, Hizbul Wathan, Nasyiatul ‘Aisyiyah, Pemuda Muhammadiyah, IPM, IMM, and Tapak Suci, significantly contributed to cadre formation, gender empowerment, youth mobilization, and civic participation. This study enriches local historiography by demonstrating Muhammadiyah’s institutional adaptability and ideological continuity across changing political regimes.